(3GdEQTGO aj Yde GdNdGa hGdLOds - (3GdYejOjs ((3eMeO Hf KGHJ Hf SYjO GdhQfjdGfi s)
(3ChdgG (B:s
(3ebOeI ai GdEQTGO Edi GdUMjM ef GdfcJ hGdaGSO efgG eJeSc GdeYdd EeG Cf jchf fUkG Ch bjGSkG s
(3BNQgG (B:s
(3hbO ESJhajfG JeGe GdcdGe ai cd WQa efgG hGddg CYde JeJ GdebOeI HMeO Gddg s
(3GdfSNI HgG MhGTs
(3cJHgG GdfGSN ef fSNI CMeO Hf GdMSjf Hf SYjO GdeOjfi hbGHdgG HfSNI YjSi Hf eMeO Hf GdEeGes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B69s
Keywords: (3GdadSaI hGdefWbs